NSUN2 knockdown ameliorates hepatic glucose and lipid metabolism disorders in type 2 diabetes mellitus through the Inhibition of ACSL6 m5C methylation - Xianshu Jiang; Xuelan Cheng; Qiu Wan (Lipids in Health and Disease)
Abstract Background Hyperglycemia and dyslipidemia characterize type 2 diabetes mellitus (T2DM). The impact of 5-methylcytosine (m5C) on liver glucose and lipid regulation in T2DM is unclear. In this study, the regulation of liver glucose and lipid metabolism by m5C methylation in a T2DM model was investigated. Methods C57BL/6 mice developed T2DM via a high-fat diet (HFD) and streptozotocin (STZ) administration. Quantitative real-time PCR was performed to assess m5C-associated gene expression in HFD-fed mice and NSUN2 levels in clinical samples. Glucose metabolism was assessed via glucose metabolism function tests. Lipid metabolic parameters were evaluated through pathological analysis and measurements of biochemical indicators in HFD-fed mice. Mechanistic investigations utilized methylated RNA immunoprecipitation (MeRIP), RNA immunoprecipitation (RIP) and RIP. Results NSUN2 expression was significantly upregulated in both T2DM clinical samples and HFD-fed mice. NSUN2 knockdown enhanced glucose tolerance and pyruvate metabolism, ameliorated insulin resistance, and suppressed hepatic lipid accumulation in HFD-fed mice. Mechanistically, NSUN2 depletion reduced ACSL6 expression by inhibiting m5C modification of ACSL6 mRNA. Furthermore, the metabolic improvements in HFD-fed mice following NSUN2 knockdown were partially reversed by ACSL6 overexpression. Conclusion This study demonstrated that NSUN2 mediates glucose and lipid metabolism dysregulation in the liver during T2DM through m5C-dependent ACSL6. These findings highlight NSUN2 as a viable target for innovative T2DM treatments.